Formation of Hierarchical Porous Nickel Oxide Nanoparticles by Green Synthesis - K. Khalugarova; Yu. M. Spivak; V. A. Moshnikov (Известия высших учебных заведений России: Радиоэлектроника, 2024)
Introduction. Porous metal oxide nanoparticles are of great scientific and technological importance due to their wide range of applications. Such materials are obtained by co-deposition, sol-gel, microemulsion, hydrothermal, vapor-phase, etc., methods. Currently, porous metal oxide nanoparticles can be obtained by green synthesis from plant extracts.Aim. Development of a scalable technique for obtaining porous nickel oxide nanoparticles with a high specific surface area. Investigation of the process of forming hierarchical porous nickel oxide nanoparticles by green synthesis.Materials and methods. Nickel oxide nanoparticles were obtained by green synthesis using an extract of Fumaria officinalis, a medicinal plant. The chemical composition and surface microstructure were studied by X-ray phase analysis, scanning and transmission electron microscopy. The parameters of the resulting porous structure, such as specific surface area, volume, and pore size, were investigated by the methods of thermal desorption and BET.Results. Large porous agglomerates ranging in size from several to tens of micrometers were obtained. It was shown that centrifugation rate can be used to vary the specific surface area of structures (up to values of Ssa = 130 m2 /g). Annealing temperature can also be used to manage the specific surface area of particles. When an optimal temperature is selected, an almost complete removal of organic ligands that stabilize nanoparticles can be achieved. A model for obtaining a developed porous structure by green synthesis is proposed.Conclusion. Hierarchical porous nickel oxide nanoparticles were obtained by the method of green synthesis using a Fumaria officinalis extract. A technique for obtaining porous nickel oxide nanoparticles with a high specific surface area was developed. It is shown that technological parameters, such as centrifugation rate and annealing temperature, affect significantly the structure and specific surface area of porous nickel oxide nanoparticles. Systems made of porous nanoparticles are promising for use as catalysts, adsorbents, and electrodes, as well as magnetic and photovoltaic materials. Such aggregated nanoparticles are also promising for use in incorporated and encapsulated nanocomposites, and for creating specialized growth platforms.